Bioaccumulation Experiments in Mussels Contaminated with the Food-Borne Pathogen Arcobacter butzleri: Preliminary Data for Risk Assessment. (12th September 2013) - Ottaviani, Donatella; Chierichetti, Serena; Rocchegiani, Elena; Bartolini, Chiara; Masini, Laura; Santarelli, Sabrina; Leoni, Francesca
Abstract : The aim of this study was to evaluate, at a laboratory scale, the ability of this microorganism to grow in seawater and bioaccumulate in mussels ( Mytilus galloprovincialis ) maintained in constantly aerated tanks, containing twenty litres of artificial seawater. Three concentrations of A. butzleri LMG 10828 T were tested (about 5 × 10 6  CFU/mL, 5 × 10 4  CFU/mL, and 5 × 10 2  CFU/mL). Following contamination, enumeration of A. butzleri was performed from water and mussels each day, for up to 96 h. Three contamination experiments with artificial seawater in absence of mussels were also performed in the same manner. In the experiments with mussels, A. butzleri declined in water of approximately 1 log every 24 h from the contamination. In artificial seawater without mussels the concentration of A. butzleri remained on the same logarithmic level in the first 48 h and then decreased of about 1 log every 24 hours. In mussels, the concentration was approximately 2 log lower than the exposition level after 24 h from the contamination, and then it decreased exponentially of 1 log every 24 h. Our findings suggest that in the experimental conditions tested A. butzleri is neither able to effectively grow in seawater nor bioaccumulate in mussels, at least in the free and cultivable form.